2020
DOI: 10.3390/ijms21145138
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of the Novel PIM Kinase Inhibitor KMU-470 in RAW 264.7 Cells through the TLR4-NF-κB-NLRP3 Pathway

Abstract: PIM kinases, a small family of serine/threonine kinases, are important intermediates in the cytokine signaling pathway of inflammatory disease. In this study, we investigated whether the novel PIM kinase inhibitor KMU-470, a derivative of indolin-2-one, inhibits lipopolysaccharide (LPS)-induced inflammatory responses in RAW 264.7 cells. We demonstrated that KMU-470 suppressed the production of nitric oxide and inducible nitric oxide synthases that are induced by LPS in RAW 264.7 cells. Furthermore, KMU-470 inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
2
18
0
Order By: Relevance
“…Previous studies showed that, both palmitate and LPS induce NLRP3 inflammasome activation ( 7 , 27 ), we therefore examined the inflammasome components in this study- NLRP3, ASC, pro-caspase-1, cleaved-caspase1 (c-caspase-1), and IL-1β. LPS or palmitate treatment increased the expression of all the components while GB extract reduced them, suggesting that the GB extract can reduce inflammasome formation ( Fig 6A and B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that, both palmitate and LPS induce NLRP3 inflammasome activation ( 7 , 27 ), we therefore examined the inflammasome components in this study- NLRP3, ASC, pro-caspase-1, cleaved-caspase1 (c-caspase-1), and IL-1β. LPS or palmitate treatment increased the expression of all the components while GB extract reduced them, suggesting that the GB extract can reduce inflammasome formation ( Fig 6A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…RAW264.7 cells were grown in Dulbecco's modified Eagles medium (HyClone) supplemented with 10% fetal bovine serum and 1% penicillin/streptomycin (HyClone). LPS (50 ng/ml) or 250 µM palmitate were used to induce inflammation as previously described ( 7 , 18 , 19 ) and 50 µg/ml LPS or 2 mM palmitate were used to induce cell death (20, 21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 110 ] A growing number of studies have demonstrated a crucial pathophysiological role in MS and EAE for MMP2, [ 111 ] MMP9, [ 112 ] and P2Y12 receptor signaling [ 113 ] and revealed an anti‐inflammatory effect of PIM1/2 inhibition through suppressing NF‐ κ B signaling. [ 114 ] Corroborating this idea, all publications administering PJ34 in the presence of PARP1 KO observed PARP1‐independent effects. [ 109 ] The promiscuous inhibition of a growing number of off‐targets by PJ34 makes it difficult to interpret its biological effects on MS and EAE.…”
Section: Role Of Parp1 In Eae Disease Severity and Pathologymentioning
confidence: 97%
“…For immunoblot analysis, LPS-stimulated cells were washed twice with ice-cold PBS. Total proteins were isolated from the cells using a lysis buffer with cocktails of protein inhibitors and then harvested with a cell scraper [33]. Total cellular protein was quantified using the Bradford assay.…”
Section: Western Blot Analysismentioning
confidence: 99%